Burning down the house : Talking Heads and the New York scene that transformed rock - Gould, Jonathan, 1951- (Mariner Books, 2025)
""Psycho Killer." "Take Me to the River." "Road to Nowhere." Few artists have had the lasting impact and relevance of Talking Heads. One of the foundational bands of downtown New York's 1970s music scene, Talking Heads have endured as a musical and cultural force for decades, their unique brand of transcendent, experimental rock a lingering influence on popular music-despite having disbanded over thirty years ago. Now on the 50th anniversary of the band's formation, acclaimed music biographer and contributor to The New Yorker Jonathan Gould offers the definitive story of Talking Heads-a band whose sound, fame, and legacy forever connected the avant-garde to rock music.From their art school origins, to the enigma of David Byrne, to the internal tensions that ultimately brought them down, Gould tells the story of a band that emerged back when rock music was still young and unwittingly redefined the era's expectations of what a rock band could sound, look, and act like. At a time when guitar solos, lead singer swagger, and sweaty stadium tours reigned supreme, Talking Heads were pretentious, awkward, infectious, distinctive-most comfortable on the ragged stages of the East Village where they could make art for themselves, above all else. More than just a biography of a band, Gould masterfully captures the singular time and place that incubated and nurtured this original music-downtown in the 1970s-that much romanticized, little understood moment in New York City history when art, music, and commerce uneasily collided to cement the post-Woodstock generation of rock stars, often with messy results. What emerges is an expansive portrait of a band and a scene that permanently shifted the horizons of popular music, iconoclasts that pushed the cultural fringe into the mainstream and then burned down the house"--